2021
DOI: 10.1111/odi.13788
|View full text |Cite
|
Sign up to set email alerts
|

Identification of circ_0089153/miR‐608/EGFR p53 axis in ameloblastoma via MAPK signaling pathway

Abstract: Objectives: This study investigated the role of circular RNAs (circRNAs) in the pathogenesis of ameloblastoma (AB), identifying potential novel targets for future targeted therapy. Materials and Methods:CircRNA and microRNA (miRNA) profiling in AB were built with microarrays. Six novel circRNAs were validated, circ-miRNA networks were delineated. Hsa-miR-608 was filtered over cross-comparison between database screening, miRNA microarray and validated. Circ-miRNA binding sponge was validated via luciferase repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 62 publications
2
12
0
Order By: Relevance
“…Our results showed that circ_0089153 is overexpressed in colorectal primary tumors and CRC cells. In agreement with our findings, dysregulation of circ_0089153 has been reported in ameloblastoma and breast cancer [ 40 , 41 ]. Moreover, Li et al .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results showed that circ_0089153 is overexpressed in colorectal primary tumors and CRC cells. In agreement with our findings, dysregulation of circ_0089153 has been reported in ameloblastoma and breast cancer [ 40 , 41 ]. Moreover, Li et al .…”
Section: Discussionsupporting
confidence: 93%
“…Our results showed that circ_0089153 is overexpressed in colorectal primary tumors and CRC cells. In agreement with our findings, dysregulation of circ_0089153 has been reported in ameloblastoma and breast cancer [40,41]. Moreover, Li et al uncovered that circ_0089153 functioned as an oncogenic driver in papillary thyroid cancer by sponging miR-145 to induce E-box binding homeobox 2 (ZEB2) expression [42].…”
Section: Discussionsupporting
confidence: 91%
“…For example, toosendanin (TSN) upregulates miR-608 and inhibits downstream targets, including Notch1 and Notch2 (41). In addition, circRNAs can also interact with miR-608, and Liu et al (42) revealed that a circ_0089153/miR-608/ EGFR/p53 interaction pathway exists in ameloblastoma (AB). The biological function of circ_0089153 relies on the MAPK signaling pathway (42).…”
Section: Regulation Of Mir-608 Expressionmentioning
confidence: 99%
“…Among these transmembrane proteins, EGFR is especially important because EGFR can interact with epidermal growth factor (EGF) and induce receptor dimerization and tyrosine autophosphorylation, resulting in cell proliferation. Both Liu et al (42) and Zhang et al (17) reported that EGFR is a target of miR-608 and that miR-608 can indirectly attenuate cell proliferation by inhibiting EGFR. Moreover, MMP-15, another transmembrane protein, binds to miR-608 and participates in the progression of AML.…”
Section: Mir-608 and Transmembrane Proteinsmentioning
confidence: 99%
See 1 more Smart Citation